Multi-repeat sequences identification using genome mining techniques for developing highly sensitive molecular diagnostic assay for the detection of Chlamydia trachomatis [version 2; peer review: 2 approved] - Shiluli, C.; Kamath, S.; Kanoi, B.N.; Kimani, R.; Maina, M.; Waweru, H.; Kamita, M.; Ndirangu, I.; Abkallo, Hussein M.; Oduor, Bernard; Pamme, N.; Dupaty, J.; et al. (F1000 Research Ltd, 2024)
Chlamydia trachomatis (C. trachomatis) is a common sexually transmitted infection (STI). In 2019, the World Health Organization reported about 131 million infections. The majority of infected patients are asymptomatic with cases remaining undetected. It is likely that missed C. trachomatis infections contribute to preventable adverse health outcomes in women and children. Consequently, there is an urgent need of developing efficient diagnostic methods. In this study, genome-mining approaches to identify identical multi-repeat sequences (IMRS) distributed throughout the C. trachomatis genome were used to design a primer pair that would target regions in the genome. Genomic DNA was 10-fold serially diluted (100pg/μL to 1×10-3pg/μL) and used as DNA template for PCR reactions. The gold standard PCR using 16S rRNA primers was also run as a comparative test, and products were resolved on agarose gel. The novel assay, C. trachomatis IMRS-PCR, had an analytical sensitivity of 4.31 pg/µL, representing better sensitivity compared with 16S rRNA PCR (9.5 fg/µL). Our experimental data demonstrate the successful development of lateral flow and isothermal assays for detecting C. trachomatis DNA with potential use in field settings. There is a potential to implement this concept in miniaturized, isothermal, microfluidic platforms, and laboratory-on-a-chip diagnostic devices for reliable point-of-care testing.